Model Fraud Hexagon untuk Mengidentifikasi Kecurangan Laporan Keuangan - Pratiwi Harmawati; Dewi Kurnia Indrastuti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the influence of independent variables on fraudulent financial statements. The independent variables analyzed include financial stability, financial targets, external pressure, personal financial needs, collusion, capability, nature of the industry, effective monitoring, ego, and change in auditor. The sample consists of 121 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023, totaling 363 data points. The methods used are purposive sampling and logistic regression. The analysis results indicate that the Nature of Industry shows a negative effect on fraudulent financial statements. Higher receivables tend to reduce the risk of fraudulent financial statements, as they require comprehensive disclosure and in-depth analysis, enhancing creditor oversight. Meanwhile, Financial Stability, Financial Targets, External Pressure, Personal Financial Needs, Collusion, Effective Monitoring, Capability, Ego, and Change in Auditor do not significantly influence fraudulent financial statements.